2017
DOI: 10.35194/jmtsi.v1i0.59
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Efikasi Diri dan Ekspektasi Pendapatan, Terhadap Minat Berwirausaha Siswa SMK (SMK Al-Madina)

Abstract: Cianjur regency is an area that has the potential to develop the regional economy through creative industries-based entrepreneurship. Cianjur is supported by many vocational schools (SMK) with relevant expertise fields to develop regional potential through entrepreneurship. Based on this, it is very important to develop entrepreneurship interest in SMK students in Cianjur by identifying factors that influence student entrepreneur interest. Factors of entrepreneur interest identified in this research are self e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…The results of this research are in line with the results of previous research examined by Sennang (2017) which found that self-efficacy has a significant influence on vocational school students' interest in entrepreneurship. Likewise, research by Muslihudin and Ilmaniati (2017) found that self-efficacy has a significant influence on interest in entrepreneurship, the higher a student's confidence or self-efficacy, the higher his interest in entrepreneurship. The results of this research are also in line with the results of Evaliana's (2015) research which found that self-efficacy has a significant influence on students' interest in entrepreneurship as well as being the dominant variable that influences students' interest in entrepreneurship.…”
Section: ______mentioning
confidence: 99%
“…The results of this research are in line with the results of previous research examined by Sennang (2017) which found that self-efficacy has a significant influence on vocational school students' interest in entrepreneurship. Likewise, research by Muslihudin and Ilmaniati (2017) found that self-efficacy has a significant influence on interest in entrepreneurship, the higher a student's confidence or self-efficacy, the higher his interest in entrepreneurship. The results of this research are also in line with the results of Evaliana's (2015) research which found that self-efficacy has a significant influence on students' interest in entrepreneurship as well as being the dominant variable that influences students' interest in entrepreneurship.…”
Section: ______mentioning
confidence: 99%
“…(Domínguez & Bezanilla, 2021;Ghatak et al, 2020). The confidence that entrepreneurs have in managing themselves and their potential and facing failures that may occur as an evaluation material for running a business for better future (Ilmaniati & Musihudin, 2017;Wang et al, 2019).…”
Section: Self-efficacymentioning
confidence: 99%
“…The desire to become an entrepreneur is a mental statement that is owned by a person to plan and survive in a business from the smallest scale (Ayyubi, Setyanti, & Surroso, 2018;Thelken & Jong, 2020;Ilmaniati & Musihudin, 2017;Youssef, Boubaker, Dedaj, & Carabregu, 2021;Hyytinen, 2021) while Digital entrepreneurship is a business or business that is run by digital media or the internet in the form of social media, blogs, websites, and so on (Yeh, Wang, Hsu, & Lin, 2020;Dewi & Haryanto, 2017;Sitinjak, 2019;Ghatak, Chatterjee, & Bhowmick, 2020;Nzembayie et al, 2019;Fisch et al, 2021). To conclude, digital entrepreneurship intention is a desire from someone to run a business digitally or utilize digital technology.…”
Section: Introductionmentioning
confidence: 99%
“…Artinya seorang wirausaha harus mampu dan yakin bahwa dirinya bisa menjalankan sebuah bisnis. Riset yang pernah dilakukan terkait efikasi diri terhadap minat wirausaha pernah dilakukan oleh (Ilmaniati, 2017) yang menemukan hasil positif signifikan. Artinya semakin tinggi efikasi yang dimiliki seseorang, maka semakin besar pula minat seseorang untuk menjadi wirausaha.…”
Section: Pendahuluanunclassified